DRESS AND CLOTHING PRACTICES IN THE HEBREW BIBLE - Alex, Jolly (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Clothes are the forte of human beings and are reflective of their intellectual and moral superiority as well as distinction from other creatures of the animal kingdom. There has been arguments and debates regarding the evolution of clothing and the origin of the textile industry. This is because the significance of clothing extends far beyond being merely a material covering for the flesh but it also serves as a cultural marker which aids in distinguishing between races, gender and social status. There lies a rich history of clothing practices among the numerous civilizations and cultures mentioned in the Old Testament of the Bible. There is a vast store of information waiting to be unraveled from these seemingly insignificant mention of various apparels and its utility in the Hebrew Bible. The reason being, clothing is intrinsically dynamic and socio-culturally efficacious and hence it warrants a serious and intentional scholarship in order to unpack the social and material impact it conceals within itself. In the Old Testament, dress possesses multiple functions - literary, rhetorical and metaphorical. For a scholar of the past, a dress is of tremendous significance because of the informational value it contains, connecting us to a past which no longer exists. This study of the genesis of clothing and related paraphernalia chiefly centres on the evolution, practice and accessibility of clothing and textiles in human history from a Biblical perspective.